Effect of flapping-meridians combined with thunder-fire moxibustion on upper limb dysfunction after stroke - Feng-Guang GUAN; Qiu-Lu JI; Yue-Qing JIANG; Zhuo-Mei ZHUANG; Xiao-Qin LIAN (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of the study is to explore the effect of flapping-meridians combined with thunder-fire moxibustion in the treatment of upper limb dysfunction after stroke. Materials and Methods: This randomized, single-blind, controlled trial included 140 patients with stroke. According to the random number table, the patients were divided into four groups: the control group (receiving conventional nursing alone), the intervention group 1 (receiving conventional nursing combined with flapping-meridians), the intervention group 2 (receiving conventional nursing combined with thunder-fire moxibustion), and the intervention group 3 (receiving conventional nursing, flapping-meridians, and thunder-fire moxibustion). All four groups were intervened 4 weeks, 6 days a week. The outcome indicators (Fugl-Meyer Assessment of the upper extremity and body mass index of shoulder abduction, elbow extension, and wrist flexion) were assessed at the beginning and the end of treatment. Results: The effect of the intervention group 3 was better than that of the intervention group 2, intervention group 1, and control group (P < 0.05). Conclusion: The flapping-meridians combined with thunder-fire moxibustion can significantly improve the upper limb motor function and muscle strength of stroke patients with hemiplegia, and its effect is better than that of single treatment.